Concrete with coconut fibre treated with sodium hypochlorite – compressive and flexural strength / Norisham Ibrahim and Muhammad Hafizhin Abdul Halim - Ibrahim, Norisham; Abdul Halim, Muhammad Hafizhin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Concrete needs to be reinforced to improve its engineering qualities. Coconut fibres were employed for this study since they are widely accessible and come in big numbers. The study compares the qualities of plain concrete and concrete reinforced with coconut fibre based on a laboratory experiment. Better management of these waste fibres will result from using coconut fibres. Two types of coconut fibre treatment were employed – treatment with tap water and treatment with sodium hypochlorite. It is found in this study that adding 1% of coconut fibre does not increase the concrete strength after 7 and 14 days of curing. However, it was discovered that using 1% coconut fibres treated using tap water increased the compressive and flexural strength of the concrete after 28 days of curing by roughly 4% and 3%, respectively. Compressive and flexural strength development agrees very well with each other. Hence, it is concluded that 1% was the ideal fibre concentration (by weight of cement) to obtain a better 28th day of compressive and flexural strength, although not for 7 and 14 days. However, concrete with the highest strengths demonstrated a very low slump value, only 20 mm. A smaller or bigger slump value showed smaller concrete strengths.